Engagement : Transforming Difficult Relationships at Work - Bolman, Lee G.; Gallos, Joan V. (New Jersey, 2016)
The book advocates that deeply engaging self, other, and the situation is the best route to transform difficult relationships. It draws from two basic premises :People always have more options for handling difficult situations than they recognize. The book is built around a simple parable that illustrates four basic rules of engagement for staying alert, grounded, and productive in the face of difficult relationships.
mck 17/08/2022
Loan